Early mobilization in the critical patient (Research, Society and Development, 2023)
Early mobilization plays a crucial role in promoting the functional independence and psychological well-being of ICU patients. This work aims to identify what is included in the national scientific production on early mobilization of critically ill patients. Literature review study. The search was carried out in the virtual library Pubmed, BVS and Scielo. The filters inserted for the search were: national and international works, complete and available in Portuguese and English, which discussed the theme proposed for the study, from 2017 to 2022. 4 articles were found in Scielo; 10 articles in PubMed and 30 in VHL. 17 articles were selected and the rest discarded by title. After the complete reading of the articles, 10 were included for the preparation of this article. Separating into 3 categories, which are: Importance of Mobilization in critically ill patients; The role of the physiotherapist in mobilization of critically ill patients in the ICU and Conflicting views on contraindications and their mobilization criteria. It is concluded that the use of early mobilization as a therapy for patients admitted to the ICU has proven to be safe and effective, as it mitigates the negative impacts associated with prolonged periods of bed rest.